THE EFFECT OF DIFFERENT SHADE LEVELS ON THE GROWTH OF THE SHORTHAND GRASS Stenotaphrum secundatum ON REGOSOL SOILS - S. A., Tarigan,; Roni, N. G. K.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika, 2024)
The availability of feed in quantity, quality and continuity is an important factor in supporting the success of livestock development. In conditions like this, the availability of existing land can be utilized optimally to be the right choice. This study aims to determine the effect of different shade levels on the growth of Stenotaphrum secundatum grass on regosol soils. This research was conducted in Sading Village, Mengwi District, Badung Regency and the research took place from July to September 2023. The design used was a complete randomized design (RAL) consisting of four treatments and each repeated seven times, so that there were 28 experimental units. The treatment is: N0: 0% shade (without paranet); N1: 20% shade (1 layer paranet); N2: 40% shade (2 layers paranet); N3: 60% shade (3 layers paranet). The variables observed are plant lenght, number of leaves, number of tillers, leaf color, leaf chlorophyll and leaf area per pot. The results showed that different shade levels had an effect on growth variables. Different shade level treatments can affect plant lenght growth, number of leaves, number of saplings, leaf color, and leaf area per pot, but not yet on leaf chlorophyll. It can be concluded that a shade rate of 40% provides the best growth of Stenotaphrum secundatum grass on regosol soils.